ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING DAN PENENTUAN HARGA JUAL DENGAN PENDEKATAN COST-PLUS PRICING (STUDI KASUS PADA RUMAH PRODUKSI WAN TEMPEH) - Amalia, Mekar Meilisa; Marviana, Ratna Dina; Sumekar, Aried (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
The purpose of this study is (1) to find out the difference between the calculation of the cost of production that has been carried out by the Wan Tempeh Production House using the full costing method, (2) to determine the difference in the determination of the selling price of the Tempeh Wan Production House by the cost-plus pricing method. Source of data comes from primary data and in the form of numbers (quantitative). Data obtained by interview, observation and documentation. To answer the problem statement, a descriptive analysis method is used.The results obtained are (1) there is a difference in the calculation of the cost of production according to the company using the full costing method. The reason is because the company has not yet implemented the calculation of production costs in accordance with the theory of cost accounting, which includes elements of direct raw material costs, direct labor costs and factory overhead costs, both variable and fixed. (2) there is a difference in determining the selling price according to the company using the cost-plus pricing method. It caused by the differences in the allocation of production costs and markup determination.